Antinuclear antibody-negative systemic lupus erythematosus: How many patients and how to identify? - Hejun Li,; Yiqing Zheng,; Ling Chen,; Shunping Lin, (Archives of Rheumatology, 2022)
Objectives: This study aims to the prevalence of antinuclear antibody (ANA)-negative systemic lupus erythematosus (SLE) and their clinical characteristics in a large single-center SLE inception cohort to provide guidance for early diagnosis. Patients and methods: Between December 2012 and March 2021, the medical records of a total of 617 firstly diagnosed SLE patients (83 males, 534 females; median age [IQR]: 33+22.46 years) who fulfilled the selection criteria were retrospectively analyzed. The patients were divided into groups with ANA-negative SLE and ANA-positive SLE, or with prolonged use of glucocorticoids or immunosuppressants (SLE-1) and without (SLE-0). Demographic, clinical characteristics, and laboratory features were collected. Results: The total prevalence of ANA-negative SLE patients was 2.11% (13/617). The prevalence of ANA-negative SLE in SLE-1 (7.46%) was significantly higher than that in SLE-0 (1.48%) (p<0.01). The ANA-negative SLE patients had a higher prevalence of thrombocytopenia (84.62%) than ANA-positive SLE patients (34.27%). As with ANA-positive SLE, ANA-negative SLE also had a high prevalence of low complement (92.31%) and anti-double-stranded deoxyribonucleic acid (anti-dsDNA) positivity (69.23%). The prevalence of medium-high titer anti-cardiolipin antibody (aCL) IgG (50.00%) and anti-ß2 glycoprotein I (anti-ß2GPI) (50.00%) of ANA-negative SLE was significantly higher than that of ANA-positive SLE (11.22% and 14.93%, respectively). Conclusion: The prevalence of ANA-negative SLE is very low, but it exists, particularly under the influence of prolonged use of glucocorticoids or immunosuppressants. Thrombocytopenia, low complement, positive anti-dsDNA, and medium-high titer antiphospholipid antibody (aPL) are the main manifestations of ANA-negative SLE. It is necessary to identify complement, anti-dsDNA, and aPL in ANA-negative patients with rheumatic symptoms, particularly thrombocytopenia.